Clinical effect of toothpaste and mouth rinse containing zinc lactate on oral malodor reduction - Patcharawan Srisilapanan (2019)
© Medicina Oral S. L. C.I.F. Background: This study aimed to investigate the effect of toothpaste and mouth rinse containing 0.14% zinc lactate on the reduction of three volatile oral malodor gases. Material and Methods: Ten subjects with good health were recruited to take part in a crossover design study with a 7-day washout period. They were randomly assigned to use the test (toothpaste and rinse containing 0.14% zinc lactate) or placebo (negative control) treatment regimens within the two-week period. All subjects were asked to refrain from tooth brushing and eating in the morning prior to the gas collection periods. The assessment of malodor measured the quantity of three volatile sulphur compounds (VSCs) using an OralChromaTM device. Oral gas collecting was divided into four time periods; before breakfast and the morning oral hygiene practice (baseline); after oral hygiene at 30 minutes, 1 hour and 2 hours. After the baseline assessment, each subject used the test or placebo treatment regimen for 7 days. After 7 and 14 days, subjects returned to the study site to repeat the same procedures with different products. Kruskal-Wallis was used to analyze the mean differences of malodor gases between the two test regimens. Results: The baseline mean of total VSCs in test and control groups was 6.5±3.7 and 1.7±9.3 ng/10 ml, respectively. The percent reduction of H 2 S at 30 minutes, 1 hour and 2 hours was statistically significant (p < 0.005) in both treatments. The percent reduction of (CH 3 ) 2 S and total VSCs in both treatments after 1 hour was statistically significant (p<0.005). Conclusions: The test treatment regimen was more effective than the placebo treatment regimen.